2017
DOI: 10.7762/cnr.2017.6.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Concentration in Gestational Diabetic Women: a Case-Control Study

Abstract: Gestational diabetes mellitus (GDM) is an impaired fasting glucose condition during pregnancy. Adiponectin is a polypeptide hormone that is extensively released by adipocytes which regulates energy homeostasis and carbohydrate and lipid metabolism. In addition, adiponectin has antidiabetic and anti-inflammatory properties. The aim of our research was to study about the relationship of adiponectin levels to GDM and glucose intolerance. We selected 25 GDM women and 35 healthy pregnant subjects (18–46 years) who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
14
0
2
Order By: Relevance
“… 16 The expression of ADIPOQ , an adipocyte-derived hormone, is decreased during pregnancy and is associated with the development of insulin resistance and glucose intolerance. 17–19 Accordingly, ADIPOQ is intensely researched as a biomarker to predict the risk of developing GDM. 20 SNPs within the ADIPOQ gene may regulate adiponectin expression during pregnancy and increase the risk for GDM.…”
Section: Introductionmentioning
confidence: 99%
“… 16 The expression of ADIPOQ , an adipocyte-derived hormone, is decreased during pregnancy and is associated with the development of insulin resistance and glucose intolerance. 17–19 Accordingly, ADIPOQ is intensely researched as a biomarker to predict the risk of developing GDM. 20 SNPs within the ADIPOQ gene may regulate adiponectin expression during pregnancy and increase the risk for GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D appears to be positively associated with adiponectin gene expression and suppresses the renin-angiotensin-aldosterone system (RAAS) components secreted by adipocytes, thus contributing to increased adiponectin secretion (20)(21)(22) . Low 25-hydroxyvitamin D (25(OH)D) concentrations may then reduce the secretion of adiponectin and could be considered a risk factor for GDM and insulin resistance (13,23,24) .…”
mentioning
confidence: 99%
“…Serum adiponectin concentrations were significantly lower in patients with GDM (5.10±2.15 ng/mL versus 7.86±3.52 ng/mL, p = 0.001) than in healthy pregnant women. These outcomes showed that serum concentrations of adiponectin were significantly lower in gestational diabetic women [ 26 ]. Doruk et al investigated adiponectin levels in women with GDM and normal glucose tolerance (NGT) at 24-28 gestational weeks.…”
Section: Discussionmentioning
confidence: 99%